(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This thesis examines how four key elements—love, emotions, positive language, and the digital world—shape children’s learning and intellectual growth. The study shows that emotional safety increases curiosity; motivation, positive words strengthen self-confidence; digital tools enhance creativity when used properly. These elements work together to create a supportive learning environment that quietly influences a child’s thinking, behavior, and long-term development. The research highlights that modern education must integrate emotional support and guided digital experiences to help children reach their full potential.